Job Search Efficacy of Arts Workers in the Digital Age: Analysis of Factors and Policy Recommendations - Gemilang Dini Arrasyid; Hilmar Farid; Yola Yulfianti (Journal of Social Research, 2025)
The Cultural and Creative Industry (CCI) has a major contribution to economic and social development, but arts workers in Indonesia still face challenges in digital job search. This study aims to analyze the perception and experience of art workers towards Job Search Efficacy (JSE), which is an individual's belief in finding work effectively through digital platforms. Using a qualitative approach and Participatory Action Research (PAR) design, data was collected through in-depth interviews with ten art workers in Jakarta from various subsectors. The results showed that JSE was influenced by three main factors: personal factors (confidence, motivation, and digital literacy), social and community factors (support from family, friends, and art collectives), and technological factors (adaptability to algorithms and digital work platforms). Most of the informants said that conventional platforms such as LinkedIn or JobStreet have not supported the need for freelance and portfolio-based art work. Therefore, this study recommends four main policies: (1) contextual digital training based on the art subsector, (2) the development of art-specific digital work platforms, (3) increasing access to devices and internet connections, and (4) strengthening communities as spaces for learning and collaboration. These findings are expected to form the basis for policies to create a more inclusive and sustainable digital work ecosystem for arts workers.